2019
DOI: 10.1093/carcin/bgz112
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of permutation for cancer risk estimation in the urothelium based on genome-wide DNA methylation analysis

Abstract: The aim of this study was to establish permutation for cancer risk estimation in the urothelium. Twenty-six samples of normal control urothelium obtained from patients without urothelial carcinomas (C), 47 samples of non-cancerous urothelium without noticeable morphological changes obtained from patients with urothelial carcinomas (N), and 46 samples of the corresponding cancerous tissue (T) in the learning cohort and 64 N samples in the validation cohort, i.e. 183 tissue samples in total, were analyzed. Genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…Even in this study, the DNA methylation profile of N samples tended to differ from that of C samples on the basis of PCA and hierarchical clustering ( Figure 1a, b) . This finding is consistent with our previous data [ 10 , 15 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Even in this study, the DNA methylation profile of N samples tended to differ from that of C samples on the basis of PCA and hierarchical clustering ( Figure 1a, b) . This finding is consistent with our previous data [ 10 , 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…It is well known that aberrant DNA methylation participates in even the early and precancerous stages in different organs [ 29 , 30 ]. In particular, we have revealed that DNA methylation levels at numerous CpG sites were actually altered in non-cancerous urothelia showing no marked histological changes, but which were clearly at the precancerous stage due to field cancerization, compared to normal urothelia; thus, DNA methylation abnormalities at the precancerous stage can predict future risk or urothelial carcinogenesis [ 15 ]. Even in this study, the DNA methylation profile of N samples tended to differ from that of C samples on the basis of PCA and hierarchical clustering ( Figure 1a, b) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most genes from the HOXC cluster have been identified as hypermethylated in cancer (HOXC4, C5, C6, C8, C9) [48,[115][116][117]. Methylated regions in a gene collection that includes HOXC4 were considered important in estimating cancer risk in urothelium [117] and as part of a prognostic signature predicting survival in patients with oral squamous cell carcinoma [66]. The role of HOXC8 in breast cancer, in which silencing seems to interfere with the self-renewal, differentiation and transformation of breast cancer stem cells, is also instigated by promoter hypermethylation [48].…”
Section: Hoxb and Hoxc Genes Methylated In Cancermentioning
confidence: 99%
“…We identified cancer-specific somatic gene alterations, such as single nucleotide variations (SNVs), insertions/ deletions (indels), and copy number variations (CNVs), as previously described. 7 Furthermore, the tumor mutation burden (TMB) and copy number alterations (CNAs) were calculated using these data. The detailed method used for counting CNA is as follows; for calculating the baseline data used for count correction per amplicon, the number of leads sequenced in each of the 160-panel amplicon probe design domains was counted to calculate the reads per million (RPM) value (ie, the number of leads per one million sequence leads).…”
Section: Next-generation Sequencing-based Multiplex Gene Assay (Plementioning
confidence: 99%